Parental genetic distance and patterns in nonrandom mating and seed yield in predominately selfing Arabidopsis thaliana - Carlson, Ann L.; Gong, Hui; Toomajian, Christopher; Swanson, Robert J. (My University, 2013)
In this study, we ask two questions: (1) Is reproductive success independent of parental genetic distance in predominately selfing plants? (2) In the absence of early inbreeding depression, is there substantial maternal and/or paternal variation in reproductive success in natural populations? Seed yield in single pollinations and proportion of seeds sired in mixed pollinations were studied in genetically defined accessions of the predominately selfing plant Arabidopsis thaliana by conducting two diallel crosses. The first diallel was a standard, single pollination design that we used to examine variance in seed yield. The second diallel was a mixed pollination design that utilized a standard pollen competitor to examine variance in proportion of seeds sired. We found no correlation between reproductive success and parental genetic distance, and self-pollen does not systematically differ in reproductive success compared to outcross pollen, suggesting that Arabidopsis populations do not experience embryo lethality due to early-acting inbreeding or outbreeding depression. We used these data to partition the contributions to total phenotypic variation from six sources, including maternal contributions, paternal contributions and parental interactions. For seed yield in single pollinations, maternal effects accounted for the most significant source of variance (16.6 %). For proportion of seeds sired in mixed pollinations, the most significant source of variance was paternal effects (17.9 %). Thus, we show that population-level genetic similarities, including selfing, do not correlate with reproductive success, yet there is still significant paternal variance under competition. This suggests two things. First, since these differences are unlikely due to early-acting inbreeding depression or differential pollen viability, this implicates natural variation in pollen germination and tube growth dynamics. Second, this strongly supports a model of fixation of pollen performance genes in populations, offering a focus for future genetic studies in differential reproductive success.
Citation: Carlson, A., Gong, H., Toomajin, C., Swanson, R. (2013). Parental genetic distance and patterns in nonrandom mating and seed yield in predominately selfing Arabidopsis thaliana. Plant Reproduction, 26(4), 317-328. https://doi.org/10.1007/s00497-013-0228-5
Keywords: Mate choice; Nonrandom mating; Seed yield; Inbreeding; Diallel; Pollen competition